Modified QUICK Schemes for 3D Advection-Diffusion Equation of Pollutants on Unstructured Grids - 邢领航 严明 黄国兵 李飞 唐文坚 (Shanghai jiao tong da xue xue bao, 2012)
In the framework of finite volume method （FVM）, two modified schemes of quadratic upstream interpolation for convective kinematics （QUICK）, namely quasi-QUICK （Q-QUICK） and normal quasi-QUICK （NQ-QUICK）, for improving the precision of convective flux approximation are verified in 3D unsteady advection- diffusion equation of pollutants on unstructured grids. The constructed auxiliary nodes for Q-QUICK or NQ- QUICK are composed of two neighboring nodes plus the next upwind node; the later node is generated from intersection of the line of current neighboring nodes and their corresponding interfaces. The numerical results show that Q-QUICK and NQ-QUICK overwhelm central differencing scheme （CDS） in computational accuracy and behave similar numerical stability to upwind difference scheme （UDS）, hybrid differencing scheme （HDS） and power difference scheme （PDS） after applying the deferred correction method. Their corresponding CPU time is approximately equivalent to that of traditional difference schemes. In addition, their abilities for adapting high grid deformation are robust. It is so promising to apply the suggested schemes to simulate pollutant transportation on arbitrary 3D natural boundary in the hydraulic or environmental engineering.